Dentognathic remains of Australopithecus afarensis from Nefuraytu (Woranso-Mille, Ethiopia): Comparative description, geology, and paleoecological context. Issue 100 (November 2016) - Haile-Selassie, Yohannes; Melillo, Stephanie M.; Ryan, Timothy M.; Levin, Naomi E.; Saylor, Beverly Z.; Deino, Alan; Mundil, Ronald; Scott, Gary; Mulugeta Alene,; Gibert, Luis
Abstract: Australopithecus afarensis is the best-known and most dimorphic species in the early hominin fossil record. Here, we present a comparative description of new fossil specimens of Au. afarensis from Nefuraytu, a 3.330–3.207 million-years-old fossil collection area in the Woranso-Mille study area, central Afar, Ethiopia. These specimens include NFR-VP-1/29, one of the most complete mandibles assigned to the species thus far and among the largest mandibles attributed to Au. afarensis, likely representing a male individual. NFR-VP-1/29 retains almost all of the distinctive archaic features documented for Au. afarensis . These features include a posteriorly sloping symphysis, a low and rounded basally set inferior transverse torus, anterosuperiorly opening mental foramen, a lateral corpus hollow bound anteriorly by the C/P3 jugae and posteriorly by the lateral prominence, and the ascending ramus arising high on the corpus. Dental morphology and metrics of the Nefuraytu specimens also falls within the range of Au. afarensis . The presence of this species at Woranso-Mille between 3.330 and 3.207 million years ago confirms the existence of this species in the area in close spatial and temporal proximity to other middle Pliocene hominin taxa such as the one represented by the Burtele foot (BRT-VP-2/73) and the recently named species Australopithecus deyiremeda . This has important implications for our understanding of middle Pliocene hominin diversity.